Neurotrophic factors in the physiology of motor neurons and their role in the pathobiology and therapeutic approach to amyotrophic lateral sclerosis - Stansberry, Wesley M.; Pierchala, Brian A. (Frontiers in Molecular Neuroscience, 2023)
The discovery of the neurotrophins and their potent survival and trophic effects led to great enthusiasm about their therapeutic potential to rescue dying neurons in neurodegenerative diseases. The further discovery that brain-derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF) and glial cell line-derived neurotrophic factor (GDNF) had potent survival-promoting activity on motor neurons led to the proposal for their use in motor neuron diseases such as amyotrophic lateral sclerosis (ALS). In this review we synthesize the literature pertaining to the role of NGF, BDNF, CNTF and GDNF on the development and physiology of spinal motor neurons, as well as the preclinical studies that evaluated their potential for the treatment of ALS. Results from the clinical trials of these molecules will also be described and, with the aid of decades of hindsight, we will discuss what can reasonably be concluded and how this information can inform future clinical development of neurotrophic factors for ALS.